The mating sites of the reindeer nose bot fly: not a practical target for control - Nilssen, Arne C.; Anderson, John R. (Rangifer, 1995)
The reindeer nose bot fly Cephenemyia trompe aggregates on hilltops/mountaintops to mate. Although active only for brief periods on certain days, males have been collected only from such sites. To evaluate possible suppression of the fly population by killing males (by insecticides or traps) at such sites, the density of sites and the number of males at each site were monitored in a summer grazing area of the semidomestic reindeer host (Rangifer tarandus) in Finnmark, northern Norway. In an area of ca. 20 km2, 19 mating sites were detected and examined during 4 hours on one day. The number of males observed at most sites was 5-16 (range 3-60). Minor hilltops had few males but at some sites >20-60 flies were dispersed over an area of at least 100 m2. It is concluded that mating sites in the study area are too numerous, and also used by many beneficial non-target species, to be practical targets for control of the species.